A cross-sectional study of amebiasis among Orang Asli school children in Sekolah Kebangsaan Penderas, Pahang. / Fatin Syamimi Mohamad Zahidan - Mohamad Zahidan, Fatin Syamimi (2015)
Amebiasis also recognized as infection by Entamoeba histolytica is still ubiquitous in rural Malaysia particularly among Orang Asli school children. This infection can be transmitted through ingestion of water or food contaminated with stool that contains E. histolytica cysts. Clinical manifestations of amebiasis ranging from asymptomatic colonization of intestinal wall to amoebic colitis which was dysentery or diarrhea andinvasive extraintestinal infection can be present in the form of liver abscess. Up tothis date, knowledge about the prevalence of amebiasis among underprivileged communities such as Orang Asli was not well documented. To contribute to the better understanding about the epidemiology of this infection, a cross-sectional study has been conducted in Pahang to provide the information regarding the prevalence, possible risk factors and clinical manifestations that associated with amebiasis. Pretested questionnaire was used for collecting demographic, socio-economic, environmental and behavioral data and further analyzed using Pearson's Chi-square, univariate and multivariate analyses. A total of89 stool samples were collected from Orang Asli school children in Sekolah Kebangsaan Penderas, Pahang. All stool samples were examined by using Wheatley's trichrome stain. Thirteen (14.61%)samples were microscopically positive with E. histolytica/E. dispar complex either cysts and/or trophozoites. The prevalence of this infection discovered an age independency relationship, with higher prevalent rates were observed among those aged ~o years compared to their counterparts (15.2% vs. 14%). According to genders, the present findings discovered that there was no significant difference between boys and girls with amebiasis. However, the prevalence of E. histolytica/E. dispar complex was found high among girls to boy with the ratio of 1.79: 1. There was no possible risk factors could be found in the present study. Diarrhea (p = 0.58) and other gastrointestinal symptoms (p = 0.49) were not statistically significant with E. histolytica/E. dispar complex infection. Essentially, the present findings highlighted that E. histolytica/E. dispar complex infection is still widespread among Orang Asli school children. Further studies using molecular technique such as single-round polymerase chain reaction should be carried out in order to differentiate the morphologically identical species of pathogenic, E. histolytica from the nonpathogenic, E. dispar species. This well documented information will be an advantageous for the public health authorities to consider special planning and implementation of specific prevention and control approach to totally eradicate this infection among Orang Asli school children in rural Malaysia.